Faculty Development Interprofessional Education Curriculum (IPEC): Case-Based Learning of IPE via a Complicated Newborn Resuscitation: Baby Boy Blue - Sharon Griswold; Kimberley Montgomery; Catherine Morse; John Erbayri; Dana Farabaugh; Nina Multak; Linda Wilson; Aleksandra Sarcevic (Association of American Medical Colleges, 2014)
Abstract Introduction Interprofessional education (IPE) knowledge and skills are vitally important to develop among academic faculty. This resource serves as an integral instructional tool for faculty development to familiarize educators with the goals of interprofessional education collaboration (IPEC). This resource was designed as a faculty development instructional tool; however it is also relevant for numerous healthcare professionals or students such as: nurses, physicians, social workers, pharmacists, pre-hospital providers, nurse practitioners, and physician assistants. Methods Although the case can be utilized in many ways, two options are delineated in the resource: A video discussion of good and poor IPE examples is provided as Option 1. Option 2 is a simulation case and participants participate in the resuscitation of Baby Boy Blue. Watching the video examples after participating in the simulation case may be helpful. The case has been successfully designed to integrate IPEC guiding principles: values and ethics for interprofessional practice, roles and responsibilities, interprofessional communication, and teams and teamwork. This complex case of two critically ill patients and the family unit was designed to be medically complex and ethically and emotionally provocative. Results The resource has been very effective to highlight the challenges in communication and teamwork skills during high-stress situations. To date more than 40 faculty and approximately 100 graduate and undergraduate nursing and physician participants have participated in our interdisciplinary educational instruction courses. Participants have suggested that the application of IPE principles via a clinically challenging case has given them a greater appreciation of how IPE principles lead to improved patient care. Discussion The application of shared values, teamwork, communication, and an understanding of roles and responsibilities is an integral part of improved outcomes in our library of scenarios. All cases in the library emphasize linkage of the IPE educational experience to authentic clinical practice and teaching to establish a clear integration of how IPE can improve social and clinical outcomes.